Toilet behaviors and lifestyle factors in anorectal diseases: a cross-sectional analysis - Yazkan, Cenk; Şahin, Samet; Yavuz, Burak; Mammadov, Anar; Özcan, Önder; Dere, Özcan (Frontiers in Surgery, 2025)
BackgroundAnorectal diseases including hemorrhoids, anal fissures, and fistulas significantly impact quality of life, yet the relationship between toilet behaviors and disease development remains poorly understood.MethodsThis cross-sectional study conducted at Muğla Sıtkı Koçman University compared 211 proctology patients with anorectal diseases to 369 healthy controls. Data on demographics, toilet behaviors, hygiene practices, and lifestyle factors were collected through structured interviews.ResultsAmong 580 participants (211 patients vs. 369 controls), patients were significantly older (46.0 ± 14.0 vs. 42.2 ± 16.4 years; p = 0.002) and predominantly male (76.3% vs. 45.0%; p < 0.001). They also had higher rates of constipation (>1/week: 18.9% vs. 5.7%; p < 0.001), back-to-front wiping (59.2% vs. 45.5%; p = 0.002), and prolonged toilet sitting (>20 min: 8.1% vs. 0.5%; p < 0.001), whereas smartphone use during defecation was lower (26.1% vs. 37.4%; p = 0.001).ConclusionThis study demonstrates significant associations between specific toilet behaviors and anorectal disease development. The findings suggest that constipation frequency, wiping patterns, and prolonged toilet sitting represent modifiable risk factors, while the inverse relationship with smartphone use warrants further investigation. These results support targeted behavioral interventions in anorectal disease prevention.